2011
DOI: 10.1002/mrm.23200
|View full text |Cite
|
Sign up to set email alerts
|

Improving SNR and B1 transmit field for an endorectal coil in 7 T MRI and MRS of prostate cancer

Abstract: 1Higher magnetic field strengths like 7 T and above are desirable for MR spectroscopy given the increased spectral resolution and signal to noise ratio. At these field strengths, substantial nonuniformities in B 1 1/2 and radiofrequency power deposition become apparent. In this investigation, we propose an improvement on a conventionally used endorectal coil, through the addition of a second element (stripline). Both elements are used as transceivers. In the center of the prostate, approximately 40% signal to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 30 publications
2
43
0
Order By: Relevance
“…Compared with the use of internal loop coils for prostate MRI at 7T , the submillimeter dimensions possible with the loopless antenna enable targeted intravascular access under image guidance , not accessible to larger internal coils. Indeed, the 50‐ to 100‐μm resolution achieved here in vitro and/or in vivo are smaller than the best resolution achieved to date at 7T of 0.5 × 0.5 mm 2 , using prostate coils with similar slice thickness .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the use of internal loop coils for prostate MRI at 7T , the submillimeter dimensions possible with the loopless antenna enable targeted intravascular access under image guidance , not accessible to larger internal coils. Indeed, the 50‐ to 100‐μm resolution achieved here in vitro and/or in vivo are smaller than the best resolution achieved to date at 7T of 0.5 × 0.5 mm 2 , using prostate coils with similar slice thickness .…”
Section: Discussionmentioning
confidence: 99%
“…This is typically tested via appropriate phantoms, usually provided by the manufacturer and/or vendor of the scanner, or specifically manufactured in the laboratory [3]. Such tests include not only signal-to-noise ratio (SNR) measurements, but also, particularly in larger, inhomogeneous RF coils, the SNR homogeneity across the sample volume [4][5][6][7][8][9][10][11][12]. Even more challenging would be the QC of hybrid systems like, e.g., PET/MRI [13].…”
Section: Some Notes Concerning Quality Control In (F)mri Mrs and Nmmentioning
confidence: 99%
“…Several studies demonstrated the safety and feasibility of MR spectrocopic imaging at 7T in patients with biopsy proven prostate cancer. 7 T MRI rendered a safe and promising technology [26][27]. Another promising novelty is Correlated Diffusion Imaging (CDI).…”
Section: Imaging For Patient Selectionmentioning
confidence: 99%